PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA UMKM DI KOTA BANDA ACEH) - Mauliansyah, T Irzal Rizki; Saputra, Mulia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to determine the effect of utilization, quality, security and supporting facilities of Accounting Information Systems (SIA) on the performance of micro, small and medium enterprises. The research sample was taken by a number of MSMEs in Banda Aceh which engaged in the industry, trade and various services sectors with a total sample of 88 MSMEs. The results of the study show that: (1) The utilization, quality, safety and supporting facilities of Accounting Information Systems (SIA) together have a significant effect on company performance; (2) Utilization of Accounting Information Systems (AIS) has a significant effect on company performance; (3) Quality of Accounting Information System (SIA) has a significant effect on company performance, (4) Security of Accounting Information Systems (SIA) has a significant effect on company performance, and (5) Supporting tools of Accounting Information Systems (SIA) have a significant effect on company performance.